BioMed Central.
BioMed Central is an STM (Science, Technology and Medicine) publisher of 257 peer-reviewed open access journals. The portfolio of journals spans all areas of biology, biomedicine and medicine and includes broad interest titles, such as BMC Biology and BMC Medicine alongside specialist journals, such as Retrovirology and BMC Genomics. All original research articles published by BioMed Central are made freely accessible online immediately upon publication.
Keywords: Tijdschriftartikels